(untitled) - McGown, K. L. (Cambridge, Mass., 1979)
The book provides clear explanations of complex issues and includes helpful charts, graphs, figures, sample questionnaires, and case studies which make important points easier to grasp. The practice cases offer engaging real-world problems that test the student’s research and analysis skills.
Keywords: Marketing research,Nghiên cứu tiếp thị